2018
DOI: 10.17061/phrp27451705
|View full text |Cite
|
Sign up to set email alerts
|

Participant perspectives of a 6-month telephone-based lifestyle coaching program

Abstract: Key points •This research adds to limited qualitative research relating to participant expectations and experiences of a telephonebased lifestyle intervention in a real-world context• Coach support was the most valued aspect of the participants' experience and, despite high attrition rates, participants were primarily positive about their coaching experience• Redesigning the service to increase flexibility in follow-up and using alternative communication methods such as text messaging to arrange follow-up call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…A high level of patient acceptability, however, was reported on the addition of telephonedelivered coaching to MDT care. This is an important finding and consistent with the literature which also found the support and rapport built by the GHS coaches increased participant adherence and motivation [37]. As discussed, service limitations across SOS within Australia prohibit the intensity of follow-up practices recommended in severe obesity [11], therefore the integration of telephone-delivered coaching may present an innovate and sustainable method of suitability supporting patients in conjunction with MDT care.…”
Section: Discussionsupporting
confidence: 82%
“…A high level of patient acceptability, however, was reported on the addition of telephonedelivered coaching to MDT care. This is an important finding and consistent with the literature which also found the support and rapport built by the GHS coaches increased participant adherence and motivation [37]. As discussed, service limitations across SOS within Australia prohibit the intensity of follow-up practices recommended in severe obesity [11], therefore the integration of telephone-delivered coaching may present an innovate and sustainable method of suitability supporting patients in conjunction with MDT care.…”
Section: Discussionsupporting
confidence: 82%
“…Participants expressed a need to have choice of delivery modes, for example, telephone calls or text messages or combination of both. Their views are similar to those expressed by participants in other obesity prevention programs that suggest innovative approaches to delivering interventions [35], where text messages were considered as supplementary to telephone coaching calls [12,17,34], or where participants preferred a combination of telephone calls and/or emails with social media or online platforms due to changing needs and to enhance engagement [8][9][10]38].…”
Section: Discussionmentioning
confidence: 61%
“…In this program, the convenience of receiving stage-based advice and support via telephone calls or text messages and when participants needed them were appreciated by majority of participants. Studies that reported participants' views on delivering adult and infant obesity prevention interventions via telephone calls, text messages or apps generally report high satisfaction rating and have been regarded favorably by participants [9,11,12,16,17,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper by Passey and Stirling 5 describes a study of the feasibility of an innovative, culturally tailored smoking cessation program for Indigenous women. Other papers report on a range of approaches to engaging communities effectively in the research process, reflecting the views of participants in a lifestyle coaching program (McGill et al 6 ) and older people in a falls prevention program (Tiedemann et al 7 ), and parents' views of a high school vaccination program (Nicholl et al 8 ). Farnbach and colleagues 9 provide a review of values-based research in Australian Indigenous primary health care.…”
mentioning
confidence: 99%